Analysis of the effectiveness of energy transfer technologies at TPP considering the limitation for pollutant emissions - Dubovskoy S.V.; Kobernik V.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
A comparison of implementation info thermal power energy of Ukraine prospective projects on reconstruction and new construction of coal power-generating units at TPP using different technologies has been conducted that allow to achieve the modern standards of major air pollutants from powerful combustion plants according to Directive of the European Parliament and of the Council 2001/80/EC. It was demonstrated that the new construction of coal power-generating units using combustion technique in a circulating fluidized bed at supercritical pressure (SCP) is equieconomic provided the reconstruction of existing power-generating units of SCP including installation of the most efficient equipment in desulfurization and denitrification. However, on a competitive market, ensuring the investment attractiveness of construction projects of new power-generating units and implementation of highly effective environmental technologies at TPP needs manyfold increase of tax on emissions of major pollutants from the levels defined in accordance with the Tax Code of Ukraine. Thus, the average market selling price for electricity from TPP will grow by 32–42%.